PENGEMBANGAN MODUL PRAKTIKUM TEKNIK DIGITAL MODEL ADDIE - Amirhud Dalimunthe; Marwan Affandi; Eka Dodi Suryanto (Pascasarjana Universitas Negeri Medan, 2021)
Abstrak: Masalah yang dihadapi saat melaksanakan praktikum Teknik Digital adalah modul praktikum yang tersedia belum belum sesuai dengan kompetensi lulusan. Masalah lainnya adalah beberapa modul yang membutuhkan perbaikan. Selain itu, panduan praktikum Teknik Digital juga belum lengkap. Solusi untuk permasalahan diatas salah satunya adalah mengembangkan modul praktikum Teknik Digital. Pengembangan modul praktikum Teknik Digital dilakukan dengan menggunakan pendekatan Project Based Learning. Model ADDIE diadaptasi dalam prosedur pengembangan modul praktikum dalam penelitian ini, yang terdiri dari Analysis, Design, Development, Implementation, dan Evaluation. Prosedur penelitian meliputi beberapa tahap yaitu analisis Potensi dan masalah, Pengumpulan data, Desain produk, Validasi desain, Revisi desain, Uji coba, Revisi produk, Uji coba pemakaian, Revisi produk dan Produksi. Hasil penelitian ini diharapkan dapat meningkatkan kompetensi, keterampilan, kreatifitas dan inovasi mahasiswa. Kata Kunci: Pengembangan, Modul Praktikum, Teknik Digital, Model ADDIE. Abstract: When attending digital engineering lectures and digital engineering internship courses, students often encounter difficulties because they need to have high logic skills when producing a series of works. Imperfect learning tools is one of the reasons for the above problems. However, some facilities and infrastructure do not support the practical and theoretical learning process. One of them is learning tools, especially practical modules that are not yet available. The purpose of this research is to develop a module and a Digital Engineering practicum jobsheet in accordance with the materials and competencies that students must achieve by utilizing the tools and materials available in the laboratory. The design of this research is R&D. The product of this research will be validated by experts and tested on students after the product is revised. The development procedure adapted from the ADDIE model developed by Dick and Carry. The data analysis technique used a simple qualitative descriptive analysis technique. This research produces a practicum module that contains work procedures and job sheets. The results of the assessment obtained from 2 media experts were 89,4% in the category of easy to understand, useful, interesting and worthy of being used as a practicum guide. The results of the assessment obtained from 2 media experts show that this module is valid and very good with an average value of 90,3%. Students using this module gave an average rating of 89% for ease of learning, attractiveness, design and benefits. Keywords: Development, Practicum Modul, Digital Engineering, ADDIE Model.